Integration of Fire Safety Barriers in the Probabilistic Analysis of Accident Scenarios Triggered by Lightning Strike on Atmospheric Storage Tanks - Benkaouha, Bilal; CHIREMSEL, Zakarya; Djamel Bellala (Journal of Failure Analysis and Prevention, 2022)
Fire safety barriers installed in atmospheric storage tanks have an important role in the prevention and the mitigation of accident scenarios triggered by lightning strike. The aim of the present study is the integration of the role of fire safety barriers in the probabilistic analysis of accident scenarios triggered by lightning strike on atmospheric storage tanks of flammable liquids. A statistical analysis of past similar accidents was performed to show their importance with respect to other naturel events such as floods and earthquakes. Depending on the tank type, different event trees are provided to describe the possible event sequences and consequences following lightning impact. Fault tree method was used to quantify the expected availability of fire safety barriers, which are integrated in event trees. The event tree related to external floating roof tanks and fault trees of safety barriers have been converted to an equivalent Bayesian network for performing sensitivity analysis, in order to identify the most critical basic elements of fire safety barriers that need to be improved. The application of the methodology to a real case study proved the importance of the integration of all relevant safety barriers performance and the influence of amelioration measures on the annual probability of lightning-triggered accidents.